1998
DOI: 10.1002/(sici)1521-4125(199811)21:11<853::aid-ceat853>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Simulation of Batch Distillation Processes by Using Orthogonal Collocation

Abstract: Orthogonal collocation on finite elements is applied to discretize the DAE system for the simulation of multiple-fraction batch distillation processes. A detailed dynamic tray-by-tray model is used to describe batch columns more accurately which, however, leads to a set of model equations composed of nonlinear DAEs with a fairly high dimension. In addition, batch distillation operation usually takes a long period of time and therefore it costs large computational expense to simulate such processes. The use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…17 Rigorous models of batch rectifiers containing differential mass balance equations and differential or algebraic energy balance equations were used for simulation and optimization studies. 3,6,7,9,18,19 Kreul et al 20 presented a rate-based model for multicomponent batch rectifiers. Along with the conventional batch rectifier, nonconventional or novel batch distillation columns have also been modeled.…”
Section: Semirigorous Modeling Of Batchmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Rigorous models of batch rectifiers containing differential mass balance equations and differential or algebraic energy balance equations were used for simulation and optimization studies. 3,6,7,9,18,19 Kreul et al 20 presented a rate-based model for multicomponent batch rectifiers. Along with the conventional batch rectifier, nonconventional or novel batch distillation columns have also been modeled.…”
Section: Semirigorous Modeling Of Batchmentioning
confidence: 99%
“…More rigorous models for multicomponent batch rectifiers based on stage-by-stage mass balance calculations were used by Noda et al, Farhat et al, Mayur and Jackson, Domenech and Enjalbert, Galindez and Fredenslund, and Bonny . Rigorous models of batch rectifiers containing differential mass balance equations and differential or algebraic energy balance equations were used for simulation and optimization studies. ,,,,, Kreul et al presented a rate-based model for multicomponent batch rectifiers.…”
Section: Semirigorous Modeling Of Batch Distillation Columnmentioning
confidence: 99%
“…For example, Panthapulakkal and Sain [10] reported that tensile strength and tensile modulus increased by 13% and 17% for hemp and glass fibers in polypropylene (PP) produced by injection molding. In another study [11], the authors reported that thermomechanical pulp fibers (40% wt.) with 10% wt.…”
Section: Introductionmentioning
confidence: 96%
“…The choice of the type of operation of distillation, as batch or continuous depends on the feed amount and on the characteristics of the feed components. The batch distillation is more commonly used due to its convenience for low volume, fine chemicals and bio chemicals [2], and its advantages like "flexibility, high product purity and possibility of multiple fraction operation [3].…”
Section: Introductionmentioning
confidence: 99%